Accelerating Inclusive KUA: Harmonization of Regulations and Integration of Cross-Sectoral Services - Ahmad Solikhun (JURNAL ILMIAH GEMA PERENCANA, 2026)
The transformation of the Office of Religious Affairs (KUA) into an inclusive religious service center is a strategic step to realize the mandate of religious moderation in Indonesia. However, this effort has faced stagnation due to a chronic gap between macro-political vision and technical operational legality at the ground level. This policy article employs a qualitative-descriptive methodology with a systematic analysis procedure that combines the study of regulatory documents and secondary data on service satisfaction. The analysis indicates that the stagnation in the inclusive KUA transformation stems from the absence of derivative regulations harmonizing cross-sectoral authority between the Ministry of Religious Affairs and the Ministry of Home Affairs. This situation is exacerbated by the dual legal regime of population administration and civil registration, which has fueled administrative uncertainty at the operational level. This article recommends the issuance of a Joint Decree (SKB) between the Ministers of Religious Affairs and the Ministers of Home Affairs as a "bridging regulation" to synchronize service protocols and legitimize SIMKAH-SIAK data interoperability. Implementation of this SKB is predicted to eliminate sectoral egos, provide legal protection for officials, and guarantee legal certainty for all citizens in accessing public services equally and without discrimination.